A 'self‐adjustment' mechanism for mixed‐layer heat budget in the equatorial Atlantic cold tongue. (20th January 2017) - Shi, Yanyan; Wang, Bin; Huang, Wenyu
Abstract: Wind forcing is one of the most important sources for the oceanic energy cycle and is especially critical to the heat budget of surface mixed layer. The sensitivity of heat budget in the equatorial Atlantic cold tongue (EACT) region (5°S–5°N, 25°W–5°E) to wind forcing and the related mechanism are explored in this study. Based on the experiments forced by different wind forcing from both reanalysis and idealized datasets, it is revealed that the contribution ratio for each of the dominant physical processes in the heat budget is insensitive (the variations within 1% of the mean) to the variations in the local winds (the largest variation is about 20% of the mean) over the EACT region. Therefore, a 'self‐adjustment' mechanism exists in the mixed‐layer heat budget: as local zonal winds over the EACT region strengthen (weaken), both the cooling effects of turbulent mixing and the combined warming effects of surface net heat flux and zonal advection simultaneously increase (decrease) by nearly the same percentage and thus their contribution ratios are kept constant. Owing to the impact of meridional winds on each term of heat budget can be neglected, the above mechanism is also tenable under the situation when the local meridional winds change.